Social Media Under Scrutiny: A Data-Driven Study of Privacy and Security Challenges - Shaivya Dixit; Ankur Srivastava; Namrata Tripathi; Vinny Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
Social media has completely changed how individuals engage with one another and has become a crucial component of modern communication. It has made it possible for people and organizations to communicate with one another, exchange ideas and information, and create communities on a global scale. Social media has also been linked to a number of detrimental effects, including addiction, cyber bullying, false information, and the dissemination of propaganda and hate speech. As a result, it is crucial that users of social media use them properly and critically assess the content they come across online. Users should be aware of social media privacy and security concerns in order to safeguard their personal information and stop illegal access to their accounts. In this paper researchers going to found the security and privacy concern of customer while using social media and its impact on their mental health. For analyzing the data JASP software has been used. It is found that a large number of paper have been concerned of privacy and security of social media. Social media has been effected the youngster more than others. The sample size has been 350. Researchers have been collect the sample though questionnaire. Social media is causes of many crimes and unlawful activity. For resolving such type of problems researchers conducted this research on social media and its privacy and concern.